Focus group in the development of concepts for a Nursing model: experience report - Jaquiele Jaciara Kegler; Eliane Tatsch Neves; Maria Ribeiro Lacerda; Diúlia Calegari de Oliveira (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To communicate the experience of developing concepts for the construction of a care model through focus groups. Methods: An experience report on the development of concepts through remote focus groups with members of a research group from a public university in southern Brazil. Results: Focus groups were developed in which homogeneity and heterogeneity criteria were observed among participants. In addition to the concepts of the nursing metaparadigm, the concepts of care and family-centered care were developed, relevant to the nursing care model in question. Final considerations: Despite the challenges of conducting remote focus groups, they were suitable for the collective construction of concepts for a nursing care model, allowing the interaction of participants from different locations.